Influence of dynamic non-equilibrium processes on strength and plasticity of materials of transportation systems - Chausov, Mykola; Pylypenko, Andriy; Berezin, Valentyn; Volyanska, Kateryna; Maruschak, Pavlo; Hutsaylyuk, Volodymyr; Markashova, Lyudmila; Nedoseka, Stanislav; Menou, Abdellah (Transport, 2018)
New experimental results on the effect of additional force impulse loading on the variation of the initial structure of the aircraft material (alloys D16, 2024-T3, VT22) at various stages of deformation are presented and a significant enhancement of its initial plasticity is achieved. Complex investigations into the material properties after a dynamic non-equilibrium process made it possible to describe the main regularities in the nature of deformation and fracture of materials, which allowed proposing general recommendations on using the revealed physical and mechanical regularities in the evaluation of strength of aircraft structures. First published online 10 May 2017